2017
DOI: 10.1038/s41598-017-14137-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis reveals host-associated differentiation in Chilo suppressalis (Lepidoptera: Crambidae)

Abstract: The striped stem borer, Chilo suppressalis Walker (Lepidoptera: Crambidae), is one of the most serious rice pests. Besides attacking rice, it also feeds on an economically important vegetable crop, water-oat Zizania latifolia. The species feeding on water-oat has higher growth and survival rate than those on rice, suggesting their success in adaptation to the new host plant. However, little is known about the molecular mechanisms of host plant adaptation. Here we investigated the midgut transcriptome responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 59 publications
(78 reference statements)
4
34
0
Order By: Relevance
“…For instance, categories related to membrane, cuticle and ribosome are significantly enriched in Polygonia c‐album when feeding on different plant species (Celorio‐Mancera et al, ). Enrichment of cuticle‐related and developmental‐related genes when feeding on different host plants has also been reported in milkweed aphids (Birnbaum et al, ) and in several other herbivorous insects (Hoang et al, ; Mathers et al, ; Matzkin, ; Schweizer, Heidel‐Fischer, Vogel, & Reymond, ; Zhong, Li, Chen, Zhang, & Li, ), suggesting that those genes might have pleiotropic effects on detoxification processes, or might be important for structuring of gut tissues. Thickening cuticular components has been suggested to reduce the penetration of insecticides, facilitating insecticide resistance (Foster et al, ).…”
Section: Discussionmentioning
confidence: 70%
“…For instance, categories related to membrane, cuticle and ribosome are significantly enriched in Polygonia c‐album when feeding on different plant species (Celorio‐Mancera et al, ). Enrichment of cuticle‐related and developmental‐related genes when feeding on different host plants has also been reported in milkweed aphids (Birnbaum et al, ) and in several other herbivorous insects (Hoang et al, ; Mathers et al, ; Matzkin, ; Schweizer, Heidel‐Fischer, Vogel, & Reymond, ; Zhong, Li, Chen, Zhang, & Li, ), suggesting that those genes might have pleiotropic effects on detoxification processes, or might be important for structuring of gut tissues. Thickening cuticular components has been suggested to reduce the penetration of insecticides, facilitating insecticide resistance (Foster et al, ).…”
Section: Discussionmentioning
confidence: 70%
“…The gut is the first defence barrier against pathogens and toxins acquired through food [2,62]. Well-characterized families of enzymes that play crucial roles in detox pathways, such as GST, UGT, and CYP proteins and peroxidases, were identified as DEGs here and in previous studies on Lepidoptera [9,12,46,61,63,64]. Most of these gene families have variable expression profiles; some transcripts are overexpressed in sugarcane-fed larvae and others overexpressed in artificial diet-fed larvae, probably due to the high structural and functional diversity of these families (Fig 5).…”
Section: Detoxificationmentioning
confidence: 75%
“…saccharalis . Tissue-specific transcriptomes of other lepidopterans have shown that despite the high variability in contig numbers, the number of protein-coding unigenes is consistently between 20,000 and 30,000 [ 9 , 12 , 46 48 ]. Insect transcriptomes have been sequenced at higher frequency in the last five years, proving to be useful as a descriptive tool and an invaluable source of sequences for studies researching gene function and design of RNAi experiments [ 2 , 10 , 13 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations